2017
DOI: 10.1007/978-3-319-54157-0_5
|View full text |Cite
|
Sign up to set email alerts
|

Automatically Configuring Multi-objective Local Search Using Multi-objective Optimisation

Abstract: Abstract. Automatic algorithm configuration (AAC) is becoming an increasingly crucial component in the design of high-performance solvers for many challenging combinatorial optimisation problems. This raises the question how to most effectively leverage AAC in the context of building or optimising multi-objective optimisation algorithms, and specifically, multi-objective local search procedures. Because the performance of multi-objective optimisation algorithms cannot be fully characterised by a single perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 19 publications
0
11
0
1
Order By: Relevance
“…Our work presented here builds on and extends two recent, more limited studies (Blot, Pernet et al, 2017;. Here, we additionally consider the bi-objective TSP, to investigate to which extent our results for the PFSP generalise to another permutation-based MOP with uncorrelated objectives.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…Our work presented here builds on and extends two recent, more limited studies (Blot, Pernet et al, 2017;. Here, we additionally consider the bi-objective TSP, to investigate to which extent our results for the PFSP generalise to another permutation-based MOP with uncorrelated objectives.…”
Section: Introductionmentioning
confidence: 94%
“…In our experiments, we will compare two SO-AAC approaches and one MO-AAC approach optimising the performance of a multi-objective local search algorithm. Specifically, as in previous work, we consider three distinct AAC approaches (Blot, Pernet et al, 2017):…”
Section: Automatic Algorithm Configuration For Multi-objective Problemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, multi-objective con gurators such as SPRINT-race [23] or MOParamILS [2] have shown the possibility and the bene ts of using multiple performance indicators. It has also been shown that, on multi-objective AAC scenario optimising multiple multi-objective performance indicators of multi-objective target algorithms, using a multi-objective con gurator should be preferred to using a singleobjective con gurator with an aggregation of the performance indicators [3].…”
Section: Automatic Algorithm Con Gurationmentioning
confidence: 99%
“…[Arroyo and Armentano 2005] propõem uma abordagem com busca local para otimizar dois pares de objetivos: (i) makespan e maximum tardiness; e (ii) makespan e total tardiness. A proposta em [Blot et al 2017]é o uso de ILS (Iterated Local Search) para otimizar makespan e total flowtime. Em [Ishibuchi et al 2003] os autores usam uma estratégia hill climbing simples em duas frentes: primeiramente são testados dois objetivos (makespan e maximum tardiness) e, num segundo teste o FSPé considerado com três objetivos (adicionando total flowtime).…”
unclassified